Implementation of Raita Algorithm for Biography Search of Biblical Figures - Gaol, Sedihati Kayan Lumban; Manalu, Hery Buha; Purba, Bona; Ginting, Suranta Bill Fatric; Marbun, Nasib (Bahasa Indonesia, 2024)
The purpose of this research is to implement the raita algorithm as a solution for searching biographies of figures in the Bible. Raita performs string matching starting from the rightmost string pattern to the leftmost string pattern that is aligned with the sting text with a predetermined shift based on the BmBc value. Raita can be used as a solution for string matching in the search for information related to the biography of figures in the Bible. In the case study conducted in this research, Raita can complete string matching to find patterns in the text very quickly, namely with only 2 (two) shifts